Age before beauty: Bringing long-lived firms into the digital age (and beyond). Issue 10 (17th September 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Long-lived firms are those that have typically survived for more than a decade, at a global level. Often such firms have failed to fully embrace digitization, which is a key method that they can develop and improve in the global digital age. Originality: The briefing saves busy executives, strategists and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.